Rules of deception [compact disc, unabridged] - Reich, Christopher, 1961- (Random House Audio, 2008)
While skiing in the Swiss Alps, surgeon Dr. Jonathan Ransom and his wife Emma are caught in terrible weather. When Emma falls and breaks her leg, Jonathan goes to get help, only to return to find Emma's lifeless body at the bottom of a steep crevasse. While investigating her death, Jonathan finds himself at the center of a global terrorist conspiracy. It becomes clear that his beloved Emma was more than what she seemed.